Molecular Association of the Arabidopsis ETR1 Ethylene Receptor and a Regulator of Ethylene Signaling, RTE1 - Dong, Chun-Hai (American Society for Biochemistry and Molecular Biology, 2010)
The plant hormone ethylene plays important roles in growth and development. Ethylene is perceived by a family of membrane-bound receptors that actively repress ethylene responses. When the receptors bind ethylene, their signaling is shut off, activating responses. REVERSION-TO-ETHYLENE SENSITIVITY (RTE1) encodes a novel membrane protein conserved in plants and metazoans. Genetic analyses in Arabidopsis thaliana suggest that RTE1 promotes the signaling state of the ethylene receptor ETR1 through the ETR1 N-terminal domain. RTE1 and ETR1 have been shown to co-localize to the endoplasmic reticulum (ER) and Golgi apparatus in Arabidopsis. Here, we demonstrate a physical association of RTE1 and ETR1 using in vivo and in vitro methods. Interaction of RTE1 and ETR1 was revealed in vivo by bimolecular fluorescence complementation (BiFC) in a tobacco cell transient assay and in stably transformed Arabidopsis. The association was also observed using a truncated version of ETR1 comprising the N terminus (amino acids 1–349). Interaction of RTE1 and ETR1 was confirmed by co-immunoprecipitation from Arabidopsis. The interaction occurs with high affinity (K(d), 117 nm) based on tryptophan fluorescence spectroscopy using purified recombinant RTE1 and a tryptophan-less version of purified recombinant ETR1. An amino acid substitution (C161Y) in RTE1 that is known to confer an ETR1 loss-of-function phenotype correspondingly gives a nearly 12-fold increase in the dissociation constant (K(d), 1.38 μm). These findings indicate that a high affinity association of RTE1 and ETR1 is important in the regulation of ETR1.